O mundo funerário dos séculos V a VIII em Portugal: perspetivas em torno das possibilidades de rastreamento de católicos e arianos - Arezes, Andreia (2019)
On the basis of the analysis of the funeral world dated from 5th-8th centuries, I propose to explore the archaeological data available and the problems they raise, in order to question the possibilities of identification and characterization of burial spaces classified as Suevic and Visigothic, on the one hand, and Hispano-Romans, on the other. In this sense, I discuss key concepts and differentiation criteria concerning burial practices, types of materials deposited in graves, specific ways of organization and deployment options in the landscape. By confronting transformations in archaeological record with the political and religious context, I put in perspective different lines of thought and define the methodological limits of interpretation.